The ectomycorrhizal fungus Paxillus involutus converts organic matter in plant litter using a trimmed brown-rot mechanism involving Fenton chemistry - Rineau, Francois (Blackwell Publishing Ltd, 2012)
Soils in boreal forests contain large stocks of carbon. Plants are the main source of this carbon through tissue residues and root exudates. A major part of the exudates are allocated to symbiotic ectomycorrhizal fungi. In return, the plant receives nutrients, in particular nitrogen from the mycorrhizal fungi. To capture the nitrogen, the fungi must at least partly disrupt the recalcitrant organic matter–protein complexes within which the nitrogen is embedded. This disruption process is poorly characterized. We used spectroscopic analyses and transcriptome profiling to examine the mechanism by which the ectomycorrhizal fungus Paxillus involutus degrades organic matter when acquiring nitrogen from plant litter. The fungus partially degraded polysaccharides and modified the structure of polyphenols. The observed chemical changes were consistent with a hydroxyl radical attack, involving Fenton chemistry similar to that of brown-rot fungi. The set of enzymes expressed by Pa. involutus during the degradation of the organic matter was similar to the set of enzymes involved in the oxidative degradation of wood by brown-rot fungi. However, Pa. involutus lacked transcripts encoding extracellular enzymes needed for metabolizing the released carbon. The saprotrophic activity has been reduced to a radical-based biodegradation system that can efficiently disrupt the organic matter–protein complexes and thereby mobilize the entrapped nutrients. We suggest that the released carbon then becomes available for further degradation and assimilation by commensal microbes, and that these activities have been lost in ectomycorrhizal fungi as an adaptation to symbiotic growth on host photosynthate. The interdependence of ectomycorrhizal symbionts and saprophytic microbes would provide a key link in the turnover of nutrients and carbon in forest ecosystems.